Biochemical characteristics of Trichoderma atroviride associated with conidium fitness for biological control. Issue 2 (1st February 2016) - Daryaei, Amir; Jones, E. Eirian; Alizadeh, Hossein; Glare, Travis R.; Falloon, Richard E.
ABSTRACT: Effects of abiotic factors during production (temperature, nutrients, water activity, pH) on conidium fitness (quantity and quality) of Trichoderma atroviride LU132 (a key biocontrol agent) were studied. Conidia from the culturing regimes which resulted in greatest and least bioactivity against Rhizoctonia solani in dual culture assays were selected to assess effects of storage conditions on conidial fitness over time. Further studies assessed interaction effects of temperatures (20°C or 30°C) and sugars (dextrose or sucrose) on conidium germination and bioactivity as fresh conidia, or after 6 months of storage. Biochemical analyses of sugars and fatty acids were carried out to determine relationships between quality variations and cellular characteristics for conidia produced in different culturing conditions. Low trehalose content in conidia (e.g. at 20°C) was associated with the least conidium fitness, although high trehalose content did not necessarily support conidium fitness. High proportions of total fatty acids in conidia were mostly associated with the least conidium fitness. When Trichoderma was grown at high carbon to nitrogen ratio (e.g. at C:N 160:1), the total conidium fatty acids content increased. This study also indicated that the monosaccharide dextrose is metabolically optimal for T. atroviride LU132 at 20°C while the disaccharide sucrose is optimal at 30°C. These studies indicate that physical growth conditions and nutritional requirements attribute in conidium fitness of T. atroviride LU132, and provide important knowledge supporting optimum production of biocontrol agents based on T. atroviride, and possibly other similar biocontrol agents.